FTL design exploration in reconfigurable high-performance SSD for server applications - Shin, Ji-Yong; Xia, Zeng-Lin; Xu, Ning-Yi; Gao, Rui; Cai, Xiong-Fei; Maeng, Seungryoul; Hsu, Feng-Hsiung (Proceedings of the 23rd international conference on Supercomputing, 2009)
Solid-state disks (SSDs) are becoming widely used in personal computers and are expected to replace a great portion of magnetic disks in servers and supercomputers. Although many high-speed SSDs are present in the market, both the design of hardware architecture and the details of the flash translation layer (FTL) are not well known. Meanwhile, in the systems requiring high-end storages, specially tuned SSDs can perform better than the generic ones, because the applications in such environment are usually fixed. Based on the architectural design of our reconfigurable high-performance SSD prototype and by using a trace-driven simulator, we explore the key factors and tradeoffs that must be considered when designing a customized FTL. FTL related issues, such as data allocation, cleaning, and wear leveling, are analyzed in detail presenting suitable design decisions for different workload characteristics. The experimental result shows that the figures for the performance metrics will vary from several percent to more than tens of times among each other depending on the decision made for designing each FTL functionality.